Optimasi pelarut etanol air dalam proses ekstraksi terhadap kadar senyawa steroid ekstrak daun senduduk bulu (Clidemia hirta (L.) D. Don) - Yuli Nurullaili Efendi; Siti Salimah; Ajeng Izzati Saputri (Health Sciences and Pharmacy Journal, 2023)
Medicinal plants are closely related to the chemical content contained in these plants, especially biologically active substances. The content of chemical compounds found in Clidemia hirta (L.) D. Don is a compound of tannin (catecholamine dan pirogalotannin), dioxiantraquinone, steroid, saponin, glicoside dan fenol. Steroids on plants show cholesterol-lowering effects, anticarcinogenic, bioinsecticide, antibacterial, antifungi and antidiabetic. The purpose of this study was to determine the highest concentration of steroid compounds with a comparison of ethanol-water concentrations in Clidemia hirta leaf extract. Experimental design in this study used Simplex Lattice Design (SLD). Qualitative analysis of Clidemia hirta extract was performed by thin layer chromatography with a stationary phase of silica gel F254 and a mobile phase of toluene : ethyl acetate : ethanol (3:1:1). The determination of steroid concentrations is carried out by measuring the area under the curve (AUC) in densitometric. Quantitative data on steroid concentration of Clidemia hirta leaf obtained from each experiment were analyzed with the Simplex Lattice Design approach. The highest concentration of steroid compounds in the ethanol of Clidemia hirta (L.) D. Don leaves extract after optimization is found in 100% ethanol solvent.